Taare zameen par (DVD) - Khan, Aamir (New Delhi : Super Cassettes Industries, 2008)
Eight year old Ishaan's world is filled with wonders that no one else seems to appreciate. Adults are more interested in things like homework and marks, and Ishaan just can not seem to get anything right in class. When he gets into more trouble than his parents can handle, he is packed off to boarding school to be disciplined. New art teacher, Nikumbh, soon realizes that something is wrong and sets out to discover why. With time, patience and care, he ultimately helps Ishaan find himself.
1. Movie; Director's commentary -- 2. Special features.
Copyright notice on container: Super Cassettes Industries Ltd.
Accompanied by: Exclusive prints of Ishaan's final painting and Nikumbh's final painting; Ishaan's flipbook, and a pencil and sound disc of background musical score.
In container (31 cm.)
Keywords: Dyslexia